MILITARY CHESS. NOTES ON THE HEADQUARTERS OF MILITARY OPERATIONS BETWEEN 1917 AND 1923 (Tzintzun, Revista de Estudios Históricos, 2023)
The history of the Headquarters of Military Operations in Mexico has beenpractically unexplored. This article offers an approach to the creation andoperation of this territorial military organization between 1917 and 1923, whichincludes the governments of Venustiano Carranza and Álvaro Obregón, beforethe development of the Delahuertista rebellion. The military division reflectedthe difficulties of pacifying the country and political recentralization. Theseprocesses did not end with the rise of the Sonora group to power in 1920; on thecontrary, their arrival led to the development of new rebel movements, somelocal and others planned by exiles from the United States. The uprisings forcedthe federal Executive to reorganize, like a chessboard, the men who commandedthe headquarters, who almost always became political operators of the center,but also occasional accomplices of the uprisings and even leaders of them.
Keywords: Mexican revolution; post-revolution; army; Venustiano Carranza; Álvaro Obregón